MAP Kinase Cascades in Arabidopsis Innate Immunity - Rasmussen, Magnus W.; Roux, Milena; Petersen, Morten; Mundy, John (Frontiers in Plant Science, 2012)
Plant mitogen-activated protein kinase (MAPK) cascades generally transduce extracellular stimuli into cellular responses. These stimuli include the perception of pathogen-associated molecular patterns (PAMPs) by host transmembrane pattern recognition receptors (PRRs) which trigger MAPK-dependent innate immune responses. In the model Arabidopsis, molecular genetic evidence implicates a number of MAPK cascade components in PAMP signaling, and in responses to immunity-related phytohormones such as ethylene, jasmonate and salicylate. In a few cases, cascade components have been directly linked to the transcription of target genes or to the regulation of phytohormone synthesis. Thus MAPKs are obvious targets for bacterial effector proteins and are likely guardees of resistance (R) proteins, which mediate defense signaling in response to the action of effectors, or effector-triggered immunity (ETI). This mini-review discusses recent progress in this field with a focus on the Arabidopsis MAPKs MPK3, 4, 6 and 11 in their apparent pathways.